República de Chile, Tierra del Fuego, Isla Chair a Canal Brecknock / por la Marina de Chile 1901 - Argentina. Dirección General de Navegación e Hidrografía (Argentina. Ministerio de Marina, 1946)
Edición 1931. Ultima corrección . 1946 Relief shown by spot heights and hachures. Depths shown by soundings.; Includes conversion table and 8 inset maps: Canal Ocasión -- Ptos Edwards y Langlois -- I. Londonderry, Puerto Engaño -- Isla London, Puerto Townshend -- Paso Timbales -- Isla Aguirre, Pto. Quo-Vadis.; "O. Pereyra Dib." -- lower right margin.; "202." Color 1:150,000